The Role of Digital Transformation in Promoting Economic Development in Emerging Markets - Rizal Rizkiana Tamziz; Muhammad Rizal Fachrurrozi (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
The advent of digital technologies has reshaped economies worldwide, especially in emerging markets. This paper explores how digital transformation accelerates economic development by enhancing business operations, improving financial inclusion, and fostering innovation. Through case studies and data analysis, the research highlights the critical role of digital infrastructure, e-commerce, and the fintech industry in driving economic growth in developing countries. Furthermore, it discusses the challenges faced, such as digital inequality and regulatory barriers, and offers recommendations for policymakers to harness the full potential of digitalization for sustainable development.